Future, or On the Redemption of Nature after Schelling and Nietzsche - Corriero, Emilio Carlo (Religija ir kultūra, 2017)
[full article, abstract in English; abstract in Lithuanian] It is starting from the role recognized and attributed to nature by Schelling and Nietzsche that one understands the renewed relationship between being and time at the basis of the possibility for the new beginning of Western philosophy, prophesized by Heidegger in 1936. For both, the possibility of the very future passes by the necessary redemption of the past (that is an extreme liberation from its conceptual hypostatization) through a form of love for the All, which is possible to recognize only with a philosophy of nature that is able to show the “unprethinkable” ground of being and its eternal dynamics as potential potentiae. Only on the basis of this potentia potentiae of the “unprethinkable” past, the “coming event” of the future becomes possible, as well as that renewed relation between time and being, which permits a new beginning for Western philosophy.